Automatic Super-linear Self-Scaling VM-algorithm - Abbas Al-Bayati; Maha Al-Salih (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, a new self-scaling VM-algorithm for unconstrained non-linear optimization is investigated. Some theoretical and experimental results are given on the scaling technique, which guarantee the Super-linear of the new proposed algorithm.